Theoretical and experimental research to development of water‐film cooling system for commercial photovoltaic modules - Vinícius Oliveira da Silva; Julio Romel Martinez‐Bolanos; Raphael Bertrand Heideier; André Luiz Veiga Gimenes; Miguel Edgar Morales Udaeta; Marco Antônio Saidel (IET Renewable Power Generation, 2021)
Abstract This work aims at developing and validating mathematical models and empirically evaluating a water‐film cooling system for commercial photovoltaic modules. Methodologically, thermal, electrical and climatological data measured in a specific purpose on‐grid outdoor test unit were used. In this work they are used to study the improvement in the performance of photovoltaic energy production due to temperature reduction. The first‐order state‐space linear parametric model presents the best performance to predict the temperature of the uncooled photovoltaic modules, with normalised mean square error (NRMSE) of 86.75%. In contrast, the non‐linear model performance of cooled photovoltaic modules is lower, with NRMSE of 44.5%; however, the results show that the performance of the complete thermoelectric model is satisfactory, with NRMSE of 76.38%. On the other hand, empirical tests showed that the cooling system reduces temperature in 15–19%, on average, and to a maximum of 35%. In terms of power, there are average gains of 5–9%, and maximum gains of 12%. Regarding gross generation, there are average gains of 2.3–6%, and maximum gains of 12%. It was concluded that it is possible to mathematically model and predict this generation using non‐linear models with a 0.2% error between modelled and measured generation.